Robustness, redundancy, inclusivity, and integration of built environment systems: resilience quantification from stakeholders’ perspectives - Al-Humaiqani, Mohammed M.; Al-Ghamdi, Sami G. (Frontiers in Built Environment, 2024)
This study focuses on understanding the functionality of the resilience qualities (RQs) of the built environment systems (BESs) and their importance in responding to and recovering from climate change disruptions effectively. Various regulatory and engineering stakeholders participated in a questionnaire survey to assess the defined RQs, including robustness (Rb), redundancy (Rd), inclusivity (Ic), and integration (It). The responses were analyzed using inferential statistical methods. The results reveal a consensus among stakeholders on the necessity of developing a transformative capacity to address unforeseen uncertainties and climate change challenges. While most respondents expressed confidence in the robustness of BESs to withstand climate change impacts, some highlighted opportunities for improving standards to bolster resilience. The findings also underscored the widespread agreement among respondents regarding the importance of regulatory measures mandating emergency resources in various BESs. Furthermore, the adaptive capacities within BESs and associated tools are not necessarily to be currently adequate and may require enhancement. To mitigate risks, it is important to incorporate reconfigurability and spare capacity into existing systems to prevent disruptions. Most participants support efforts to promote good practices at the community level and address the impacts of climate-related events. The analysis also emphasizes the need for inclusive community consultation and engagement to foster a shared responsibility for enhancing the resilience of urban ecosystems against the impacts of climate change. This involves aligning processes across various city systems to support cohesive decision-making and strategic investments. The study suggests developing objective engineering techniques to establish a standardized approach for evaluating the RQs of BESs.